The Interpretasi Pangiket Triaji Pada Kisah Sumbadra Dan Arjuna Dalam Serat Menak Untuk Menghadapi Insecure Society - Gresiska Putri; Syafa Felisa (Universitas Negeri Surabaya, 2026)
The phenomenon of insecure society in today's young generation has given rise to an identity crisis, emotional instability, and weak foundation of values in building long-term relationships. This article aims to interpret the concept of Triaji, which includes aspects of bibit, bebet, and bobot in the story of Arjuna and Sumbadra in Serat Menak, and to examine the relevance of these symbolic values in facing the dynamics of modern society filled with anxiety and value disorientation. This study uses a qualitative interpretative approach with Clifford Geertz's symbolic anthropology theory, which emphasizes thick description in interpreting the symbolic meaning of culture contextually. The results of the study show that the concept of Triaji not only functions as a traditional guide in choosing a life partner, but also contains cultural symbols that represent cultural identity, social ethics, and emotional maturity. The characters of Arjuna and Sumbadra are represented as an ideal couple who are balanced genealogically, morally, and spiritually. The symbolic meaning of the Triaji concept in the story reflects Javanese cultural values that are still relevant and applicable as an ethical framework in building healthy, stable, and culturally conscious social relations. Thus, this article emphasizes the importance of revitalizing local symbolic meaning as an effort to answer the psychosocial and relational crisis in the era of globalization.